Trade Unionism in Central Europe - TUC Survey, 1946 (pg. 19) (1946)
1946 1945-1960 "Trade Unionism in Central Europe - TUC Survey, 1946 (pg. 19)" [hfr0123_20.jpg], 1946 In November - December 1945, a TUC delegation visited Germany, Czechoslovakia, Austria and Italy to report and advise on the re-establishment of free trade unions.